Etiology and outcome of patients with viral-induced acute liver failure - Nabi, Tauseef; Rafiq, Nadeema (International Journal of Research in Medical Sciences, 2019)
Background: Acute liver failure (ALF) is a rare medical emergency and devastating clinical syndrome associated with high mortality in the absence of immediate intensive supportive care, specific treatment, or liver transplantation. Viral hepatitis is still one of the main causes of ALF in the India as well in world. We aimed to determine the etiology of Viral-ALF and to compare the outcome and clinical and biochemical variables in patients with hepatitis E and non HEV group in this prospective study. Methods: A total of 37 patients with a diagnosis of viral-ALF were included in the study. The variables evaluated were demographic, signs and symptoms, biochemical parameters, severity of liver injury, outcome, complications and duration of hospital stay. Results: Out of 37 Viral-ALF patients, Acute HEV-induced ALF (48.6%) was most common followed by HBV (24.3%) and HAV (21.6%). There were significantly more females in HEV group (61.1%) than non HEV group (21.1%) (P = 0.014). Overall mortality was 20 (54.1%). Mortality was higher in non HEV group (73.7%) than HEV group (33.3%) (P = 0.015). The mean age in HEV group was 30±12.7 years and in non HEV group was 38.1±10.4 years (P = 0.042). Bilirubin, ALT, mean grade of coma and interval between jaundice and encephalopathy were significantly higher in non HEV group than HEV group. MELD Score was higher in non HEV group 32.6±7.9 than HEV group 26.3±7.2 (P = 0.012). Sepsis and renal failure occurred more frequently in non HEV group than HEV group. Duration of hospital stay was also significantly more in non HEV group 11.3±3.3 days versus HEV group was 7.9 ± 2.9 (P = 0.002). Conclusions: HEV was the most frequently associated with Viral-ALF. HEV related ALF disproportionately affected young women. Mortality was higher in non HEV group (73.7%) than HEV group (33.3%). The marked difference in spontaneous survival between HEV and non HEV group can be explained by the severity of hepatic dysfunction on admission and more frequent complications.